The effect of different type of fertilizer in mature oil palm / Intan Nurasmida Mohd Khairi - Mohd Khairi, Intan Nurasmida (Faculty of Plantation and Agrotechnology, 2018)
The demand in oil palm plantation nowadays is higher than the other plantation. Palm oil is the supply for the food manufacture, product cosmetic and personal care, biofuel and energy. Oil palm have the high yielding source of edible and technical oil. By using the good fertilizer, we can get the high yield and can increases the economies of oil palm. This study aimed the different fertilizer that can be effect the yield and economic in mature oil palm. The production of oil palm in plantation can increase by using the bio-organic and chemical fertilizer. This prove by FELCRA Temerloh, Pahang that applying the different types of fertilizer in their estates such as bio-organic and chemical. Data of the oil palm plantation in years 2014 to 2016 has been obtained from project Berhala Gantang 2 and analyzed. Using the T-test to get the result of production in FELCRA oil palm plantation. From the result, P-value < 0.00, so the result was significant different between using different fertilizer and the production of oil palm in FELCRA. In result, the best fertilizer that can be apply to get more yield in every month is bio-organic and chemical fertilizer compared to the chemical fertilizer only. As recommendation, applying bio-organic and chemical fertilizer may help the production of oil palm in FELCRA and others plantation in Malaysia.